What Drives Sector Allocation of Foreign Direct Investment in Iceland? - Helga Kristjánsdóttir (University of Copenhagen, Economic Policy Research Unit (EPRU), 2005)
The objective of this paper is to examine how the driving forces of investment in a small country like Iceland differ from those in larger countries. Special attention is given to the dominating investment sector in Iceland due to its resource intensity. Estimates are based on 1989-1999 panel data on foreign direct investment in various sectors. This may help explain why the investment pattern in Iceland differs from the general case.
Keywords: F21; F23; 330; foreign direct investment; multinational corporations; Direktinvestition; Schätzung; Multinationales Unternehmen; Insel